Navigating through tortuosity: “A S-shaped abdominal aorta” (Indian Journal of Case Reports, 2021)
Tortuosity of the abdominal aorta is common to encounter during transfemoral intervention in the elderly cohort but an extreme form of abdominal tortuosity assuming S-shape has not been reported so far. We report a case of an extreme form of abdominal aorta tortuosity in 65-year-old male in whom successful coronary intervention was performed with Amplatzer extra stiff (0.038) wire and larger guide catheter (EBU 7F 3.5) for good back up support. Rare to encounter, this extreme S-shaped tortuosity in a young-old patient remembers us the fact that “arteries and aorta can also kink early.”